Creating material data for thermoset injection molding simulation process. (February 2019) - Tran, Ngoc Tu; Gehde, Michael
Abstract: Thermoset material data for reactive injection molding simulation process is found in limited sources and seldom available from data bank of simulation tools because of complication not only in rheological and thermal properties measurement but also in writing optimization algorithm to model rheological and thermal mathematical equations. In this paper, rheological and thermal properties of thermoset injection molding compounds were successfully measured. In addition, a numerical method was developed to create material data of thermoset injection molding compounds, which was directly imported into a simulation tool, namely, Moldex3D to investigate its application in thermoset injection molding simulation process. Furthermore, a strong slip phenomenon on the interface between thermoset melt and wall surface which was investigated and detected during injection molding experiments was taken into account in the filling simulation process. The computation was found to be in good agreement with the experimental results, indicating that the new generated material data is reasonable and the influence of wall slip on the mold filling characterization of thermoset injection compounds during simulation process is not ignorable. Highlights: Investigating the wall slip phenomenon of thermoset materials in the injection molding process. Comparison of thermosets flow behavior with thermoplastics. Developing a numerical method for creating material data sheet for the thermoset injection molding simulation process. Simulating the mold filling characterization of thermoset injection molding compounds with slip boundary condition. Opening a new thinking about influence of slip on simulation of fiber orientation in the injection molding process.